Postnatal Care Utilization Coverage and its Associated Factors Among Mothers in South Gondar Zone, Northwest Ethiopia: A Cross-Sectional Study - Setegn Muche Fenta; Yikeber Abebaw Moyehodie; Alebachew Taye Belay; Hailegebrael Birhan Biresaw; Kenaw Derebe Fentaw; Mequanint Melkam Yalew; Mitiku Wale Muluneh; Solomon Sisay Mulugeta; Maru Mekie (SAGE Publishing, 2022)
Background Postnatal care (PNC) is critical for both the mother and the infant to treat delivery complications and provide the mother with important information on caring for herself and her baby. However, only 17% of women and 13% of newborns in Ethiopia received a postnatal checkup within the first two days of birth. This figure is significantly lower than the least developed countries. This study aimed to assess the coverage and associated factors of PNC service utilization in South Gondar Zone, Northwest Ethiopia. Method A community-based cross-sectional study was conducted from September 2020 to May 2021. The data were gathered using an interviewer-administered structured questionnaire. A total of 434 women who gave birth within 2 years of the study were included in the analysis. Bivariable and multivariable logistic regression model was used to identify factors associated with PNC service utilization. Result The prevalence of women who used PNC services was 36.4%. The study showed that antenatal care visit, husbands who have a secondary education, women with a secondary education, daily laborer women, husbands working for the government or non-profit sector, delivered in a health institution, nearby hospitals, travel by car to the nearest health facility were positively associated with PNC utilization. While, not having a cell phone, rural women and not having road access to a health facility, have not been receiving counseling were negatively associated with PNC utilization. Conclusion The coverage of PNC service utilization in the study area was extremely low. Therefore, government and health care departments should pay special attention to uneducated women, women in rural areas, and women who are unemployed, are not exposed to mass media, and do not have access to transportation to improve PNC service utilization. Furthermore, programs educating mothers on the benefits of antenatal checkups and safer places of childbirth should be considered to increase PNC service utilization.